Cover - Gonçalves, Sergio Eduardo de Paiva (Brazilian Dental Science, 2017)
Cover: Figure of the article "Influence of the occlusal contacts in formation of Abfraction Lesions in the upper premolar" Authors: : Victória Luswarghi Souza Costa, João Paulo Mendes Tribst, Alexandre Luiz Souto Borges